EMPLOYMENT ISSUES AND CHANGES IN THE 20 YEARS AFTER WORLD WAR II (Universal International Scientific Journal, 2026)
After World War II, significant changes occurred in the population of the republic: the number of children and the working-age population decreased, and the number of elderly people increased. The main reason for this is the decrease in birth rates and high mortality rates as a result of the hardships of the war years. In the pre-war years, the difference between men and women was such that there were more men. This article discusses the issues of employment of workers and employees in the Samarkand region.
Keywords: war, labor, worker, resource, population.